Identification, Isolation, and Characterization of Medipeptins, Antimicrobial Peptides From Pseudomonas mediterranea EDOX - Zhou, Lu; de Jong, Anne; Yi, Yunhai; Kuipers, Oscar P. (Frontiers in Microbiology, 2021)
The plant microbiome is a vastly underutilized resource for identifying new genes and bioactive compounds. Here, we used Pseudomonas sp. EDOX, isolated from the leaf endosphere of a tomato plant grown on a small farm in the Netherlands. To get more insight into its biosynthetic potential, the genome of Pseudomonas sp. EDOX was sequenced and subjected to bioinformatic analyses. The genome sequencing analysis identified strain EDOX as a member of the Pseudomonas mediterranea. In silico analysis for secondary metabolites identified a total of five non-ribosomally synthesized peptides synthetase (NRPS) gene clusters, related to the biosynthesis of syringomycin, syringopeptin, anikasin, crochelin A and fragin. Subsequently, we purified and characterized several cyclic lipopeptides (CLPs) produced by NRPS, including some of the already known ones, which have biological activity against several plant and human pathogens. Most notably, mass spectrometric analysis led to the discovery of two yet unknown CLPs, designated medipeptins, consisting of a 22-amino-acid peptide moiety with varying degrees of activity against Gram-positive and Gram-negative pathogens. Furthermore, we investigated the mode of action of medipeptin A. The results show that medipeptin A acts as a bactericidal antibiotic against Gram-positive pathogens, but as a bacteriostastic antibiotic against Gram-negative pathogens. Medipeptin A exerts its potent antimicrobial activity against Gram-positive bacteria via binding to both lipoteichoic acid (LTA) and lipid II as well as by forming pores in membranes. Collectively, our study provides important insights into the biosynthesis and mode of action of these novel medipeptins from P. mediterranea EDOX.